Influence of Occupant Behaviour Lifestyle on an Italian Social Housing. (November 2016) - Becchio, C.; Bello, C.; Corgnati, S.P.; Ingaramo, L.
Abstract: The Post-Carbon City concept has a decisive effect on the building design, in terms of envelope and system technologies, and, especially, of interaction between the occupant and the building itself. Occupant behaviour lifestyle is one of the most significant driving factors of uncertainty in the prediction of building energy use and thus represents a fundamental aspect that is necessary to modelling. This study examines the difference between the energy consumptions assessed during design phase and the monitored ones for a social housing. Dynamic simulation was employed to demonstrate the impact of occupant behavior lifestyles and household composition on energy uses.